Pengaruh Game Online terhadap Kemampuan Emosional Anak Usia 5-6 Tahun di Kelurahan Leok 1 Kecamatan Biau Kabupaten Buol - Grahitta Ainun Rizky; Mohamad Zubaidi; Setiyo Utoyo (Student Journal of Early Childhood Education, 2022)
The purpose of the study was to investigate the effect of online games on the emotional abilities of children aged 5-6 years in Leok 1 Village, Biau District, Buol Regency. This study is an Ex-post facto quantitative study and the number of samples is 30 children. From the results of the study, there was an effect of I on children's emotional abilities by looking at the average value of x and y. This can be seen in X obtaining an average value of 31.06 while in Y data obtaining an average value of 49.06. Based on the output of the Statistical Test, it is known that sig.n(2-tailed) is 0.000. Because the value is 0.000 0.05, the hypothesis is accepted. Thus, the research hypothesis states that there is an influence of online games on the emotional abilities of children aged 5-6 years in Leok 1 Village, Biau District, Buol Regency. The influence that arises makes children easily rebellious, cry and sulk when the use of online games is limited.